The role of psychological readiness in return to sport ssessment after anterior cruciate ligament reconstruction - Heyn Faleide, A. G. Magnussen, L. H.; Strand, T.; Bogen, B. E.; Moe-Nilssen, R.; Fleten Mo, I.; Vervaat, W.; Inderhaug, E. (The American Journal of Sports Medicine, 2021)
Background: Knowledge about the predictive value of return to sport (RTS) test batteries applied after anterior cruciate ligament reconstruction (ACLR) is limited. Adding assessment of psychological readiness has been recommended, but knowledge of how this affects the predictive ability of test batteries is lacking.